Chronic treatment with tetrahydrobiopterin reverses endothelial dysfunction and oxidative stress in hypercholesterolaemia. Issue 4 (4th October 2007) - Cosentino, F; Hürlimann, D; Delli Gatti, C; Chenevard, R; Blau, N; Alp, N J; Channon, K M; Eto, M; Lerch, P; Enseleit, F; Ruschitzka, F; Volpe, M; et al.
Abstract : Background: Reduced availability of tetrahydrobiopterin (BH4 ), an essential cofactor of nitric oxide (NO) synthase (NOS), decreases NO production and increases reactive oxygen species. Both mechanisms contribute to atherosclerotic vascular disease. Although acute supplementation of BH4 improves endothelial dysfunction, the effect of chronic BH4 in humans is unknown. Objective: To investigate the effect of chronic BH4 supplementation on endothelial function and oxidative stress in hypercholesterolaemia. Design: Randomised double-blind, placebo-controlled trial. Setting: University Hospital. Patients: 22 hypercholesterolaemic patients (low-density lipoprotein (LDL) >4.5 mmol/l) were randomised to 4 weeks of oral BH4 (400 mg twice daily) or placebo. Age-matched healthy volunteers served as controls. Main outcome measures: Endothelium-dependent and -independent vasodilatation was assessed by venous occlusion plethysmography. To elucidate the mechanisms of BH4 effect, NO release and superoxide anion (O2 − ) production were measured in human aortic endothelial cells exposed to native LDL (2.6 mmol cholesterol/l). Results: BH4 plasma levels were significantly increased by oral supplementation. NO-mediated vasodilatation to acetylcholine was reduced in patients compared with controls and restored by BH4 . No effect of BH4 on endothelium-independent vasodilatation was seen. Furthermore, 8-F2 isoprostane plasma levels, a marker of vascular oxidative stress, were reduced by BH4 . In LDL-treated endothelial cells, BH4 levels and NO release were reduced and O2 − production increased compared with control cells. Exogenous BH4 normalised NO and O2 − production. Conclusions: In hypercholesterolaemia, endothelial dysfunction and oxidative stress can be reversed by chronic oral treatment with BH4 . Thus, BH4 availability is essential for maintaining NO synthesis and low O2 − production by endothelial NOS in vivo, and may provide a rational therapeutic approach to prevent cardiovascular disease.